Primary elections between fortuna and virtù. Issue 1 (2nd January 2016) - Pasquino, Gianfranco; Valbruzzi, Marco
ABSTRACT: Primaries have become an almost indispensable tool of the political game in the Italian centre-left coalition and, especially, within the Democratic Party. This article explores what has led to this important institutional change in the candidate and leadership selection processes. It assesses the consequences with reference to both competition and inclusiveness. It concludes by stressing that, frequent, undocumented and unfounded criticisms notwithstanding, Italian primaries have played, and promise to continue to play, quite a positive role in the Italian political system.